2022
DOI: 10.1111/apa.16483
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric emergency departments should manage young febrile and afebrile infants the same if they have a fever before presenting

Abstract: Febrile infants have a relatively high risk of meningitis, bacteremia, and urinary tract infection (UTI), which are often defined as serious bacterial infections (SBIs). Studies have reported that the prevalence of SBIs was 9%-25% in febrile infants ≤60 days. [1][2][3][4][5][6] Because of this high risk, a number of guidelines have been developed to manage febrile infants. 4,7,8 Previous studies showed that almost 30% of infants brought to paediatric emergency departments (PEDs) due to fever were afebrile duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…This is in line with several studies on the management of febrile infants that have shown that well-appearing infants, infants afebrile at the PED, and infants with respiratory symptoms undergo fewer investigations and procedures. 16,[20][21][22] This observation led researchers to hypothesize that these clinical parameters might in uence physicians' decisions not to follow the recommended management guideline. [16][17][18]36 Our study supports this hypothesis and shows that the general condition, presence of fever, and suspected focus of infection seem to play a central role in physicians' decision-making process to adhere to certain steps of the guideline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with several studies on the management of febrile infants that have shown that well-appearing infants, infants afebrile at the PED, and infants with respiratory symptoms undergo fewer investigations and procedures. 16,[20][21][22] This observation led researchers to hypothesize that these clinical parameters might in uence physicians' decisions not to follow the recommended management guideline. [16][17][18]36 Our study supports this hypothesis and shows that the general condition, presence of fever, and suspected focus of infection seem to play a central role in physicians' decision-making process to adhere to certain steps of the guideline.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] Quantitative studies on management and prevalence showed that well-appearing febrile infants, infants without fever during the examination, or febrile infants seen in private pediatric o ces underwent fewer investigations and therapeutic interventions than recommended. 16,[20][21][22] Hence, researchers hypothesized that the general condition of the infant, the absence of fever, and the physicians' experience might in uence the decision not to follow guidelines. 16,17 Aronson et al, in a study with semi-structured interviews, aimed to learn the factors that in uenced physicians' decision to perform a lumbar puncture (LP).…”
Section: Introduction Page 3/18mentioning
confidence: 99%
“…We did not account for infants who had fever at home but were afebrile at ED triage. It has been reported that infants who were afebrile at presentation to the ED but had fever at home had a significant risk of meningitis and other SBIs 23 . The presence and height of fever prior to ED attendance deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the medical records of infants aged 29–90 days with a fever of ≥38°C who presented to our PED from 1 January 2018 to 31 December 2020. We enrolled patients with fever measured at home, but excluded afebrile patients whose suspected fever was only measured on arrival by touch 4,5 . The Pediatric Assessment Triage identified children who seemed well using appearance, respiratory work and circulation 4 .…”
Section: All Sbi ≤12 H Fever (Group No 1) Sbi > 12 H Fever (Group No ...mentioning
confidence: 99%
“…We enrolled patients with fever measured at home, but excluded afebrile patients whose suspected fever was only measured on arrival by touch. 4,5 The Pediatric Assessment Triage identified children who seemed well using appearance, respiratory work and circulation. 4 The pathological Step-by-Step values were: CRP >20 mg/L, procalcitonin >0.5 ng/mL and ANC >10 000 cell/mm 3 .…”
Section: Repeated Inflammatory Markers May Be Useful For Assessing Fe...mentioning
confidence: 99%